Prediction of ship added resistance in waves using an artificial neural network - Thangamuthu, Vijayazhagan (Nanyang Technological University, 2021)
Ship resistance is one of the major components of the ship which hampers its motion. This resistance value experienced by a ship should be known and overcome for the efficient operation of a vessel. This project presents a model to predict added wave resistance experienced through the aid of a Keras sequential artificial neural network. The model is trained with different parameters to enhance its accuracy. A user interface is then linked to this model to attain user inputs and predict the added wave resistance experienced by sea-going vessels.